The foreign policy of a radicalised state- the two level game of Zimbabwe's relations with the IMF (2000-2007) - Nyoni, Tavaka S (Department of Political Studies, 2014)
The suspension of Zimbabwe from the IMF's Poverty Reduction and Growth Facility (PRGF) in 2001 has been justified as resulting from loan repayment arrears and failed macroeconomic policies. This dissertation argues that these justifications oversimplify the relationship between the Fund and Zimbabwe in the 2000s. As such, three factors are essential for a more comprehensive analysis into the country's foreign policy- the state type, the impact of bargaining between factions of different ideological underpinnings (internationalists vs. nationalists), and land reform. The socio-economic context of neocolonialism and the negative impact of the Economic Structural Adjustment Programme (ESAP) on the domestic level, and comprehensive economic sanctions on the international sphere forged a radicalised state. The Land Reform and Resettlement Programme (LRRP) became the conduit through which economic redistribution occurred and the structural cleavages it created were significant in defining the political ‘rules of the game'. We argue that foreign policy analysis of a radicalised state specifically necessitates a closer look at the symbiotic synergies between domestic bargaining and international negotiation. Through the lens of Putnam's Two Level games hypothesis, we conclude that there were four main factors that determined the country's foreign policy towards the IMF and the failure of the negotiations- there was a prioritisation of domestic political considerations over external conditionalities; there was an incompatibility of ‘win-sets' between the IMF and Zimbabwe; that comprehensive sanctions reduced the IMF's bargaining space; and domestic ideological divergence between neoliberal ‘internationalists and radical ‘nationalists' undermined the negotiations.